Preadvanced Japanese - Konomi, Emiko (Open textbook library., 2014)
Preadvanced Japanese is designed for students who have intermediate competency in Japanese, roughly at Level 2 on the ILR (The Interagency Language Roundtable) proficiency scale, and are working on reaching Level 3.This textbook can be used for self-study, as part of online course, and in a traditional classroom setting. It is comprised of four chapters, intended to be covered in one term of a quarter system. Each chapter has Drills on expressions and grammar, Kanji Drills, and Listening Exercises. These activities are to be performed using the accompanying audio.